If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + n + 10 = 28 Reorder the terms: 10 + 5n + n = 28 Combine like terms: 5n + n = 6n 10 + 6n = 28 Solving 10 + 6n = 28 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6n = 28 + -10 Combine like terms: 10 + -10 = 0 0 + 6n = 28 + -10 6n = 28 + -10 Combine like terms: 28 + -10 = 18 6n = 18 Divide each side by '6'. n = 3 Simplifying n = 3
| 2x+1-x+2= | | f(x)=x^2+9x-1f(x+6) | | 9x+6=4x+101 | | 8(2K-1)=4k-28 | | -5=-2+l | | 9(2y-8)-(2y+2)= | | f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 |